P094 Textbook outcome in Inflammatory Bowel Disease surgery. (27th May 2021) - Burneikis, D; Liska, D; Lipman, J; Valente, M; Gorgun, E; Kessler, H; Hull, T; Sklow, B; Steele, S; Lightner, A; Holubar, S
Abstract: Background: Textbook outcome (TO) is a composite measure of quality representing the most ideal result that can be expected from a surgical encounter. TOs for hepatobiliary, bariatric and thoracic procedures have been described in the literature. The purpose of this study was to define and to benchmark the rates of TO for common procedures in patients with Inflammatory Bowel Disease (IBD). Methods: The American College of Surgeons National Surgical Quality Improvement Project (NSQIP) participant user files (PUF) from 2011 to 2019 were examined. Adults undergoing surgery for Crohn's disease or ulcerative colitis were included. Four index procedures were selected for the study using Current Procedural Terminology (CPT) codes: ileocolic resection (ICR), diverting loop ileostomy closure (DLIC), total abdominal colectomy (TAC), and ileal pouch construction (IPAA). Four criteria had to be satisfied completely to achieve TO: 1) no 30-day complications, 2) no unplanned return to operating room, 3) no 30-day readmission, and 4) length of hospital stay (LOS) less than or equal to a predetermined threshold for each procedure. The LOS thresholds were derived by surveying 12 colorectal surgeons at our institution about the ideal length of stay for each of index procedure. Relevant preoperative variables collected in the NSQIP PUF were analyzed with multivariable logistic regression to identify potential predictors of TO for each procedure. Results: The study included 15, 261 distinct surgical encounters containing 6, 862 ICR, 1, 149 DLIC, 3, 835 TAC and 3, 415 IPAA. The survey mean ideal LOS for each procedure was 3 days for ICR, 2 days for DLIC, 4 days for TAC, and 4 days for IPAA. Using the above definition, TO was achieved in 29% of ICR, 20% of DLIC, 46% of TAC, and 35% of IPAA. The rate of achieving TO increased over time for all four procedures studied (Figure 1). Multivariable logistic regression identified several unique positive and negative predictors of achieving TO. For ICR, male sex and ASA class 4 were significant negative predictors of TO (OR 0.73 [0.66–0.82] and 0.23 [0.07–0.86] respectively); while for TAC, older age and presence of wound infection [DL3] made TO less likely (OR 0.51 [0.35–0.75] and 0.45 [0.23–0.88] respectively); for IPAA, laparoscopic approach made TO much more likely [DL4] (OR 2.0; [1.62–2.46]). We identified no statistically significant predictors of TO for DLIC. Satisfying the LOS threshold was the greatest determinant of achieving TO for all four procedures studied. Conclusion: In this study, we present the rates of TO for the four most common IBD operations as captured in NSQIP. TO has the advantage of being easy to interpret and can be followed over time to benchmark individual and institutional performance.